2008
DOI: 10.1111/j.1365-2575.2007.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a dynamic project learning and cross‐project learning capability: synthesizing two perspectives

Abstract: Driven by the complexity of new products and services, project work has become increasingly common in all types of organizations. However, research on project learning suggests that often project teams do not meet their stated objectives and, moreover, there is limited organizational learning from the experiences of project work. We use the dynamic capabilities framework to argue that building a dynamic project learning capability is useful for organizations that make extensive use of projects. We use both sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 43 publications
(69 reference statements)
2
65
0
3
Order By: Relevance
“…Maqsood et al, 2006;Koners and Goffin, 2007;Newell and Edelman, 2008;Paranagamage et al, 2012). The majority of these studies, often implicitly, adopt a sender/receiver perspective on learning which assumes the possibility of engineering communication channels for transferring knowledge between projects and "lubricating their operation with the proper tools and motivated context" (Kasper et al, 2013, p.334).…”
Section: Introductionmentioning
confidence: 99%
“…Maqsood et al, 2006;Koners and Goffin, 2007;Newell and Edelman, 2008;Paranagamage et al, 2012). The majority of these studies, often implicitly, adopt a sender/receiver perspective on learning which assumes the possibility of engineering communication channels for transferring knowledge between projects and "lubricating their operation with the proper tools and motivated context" (Kasper et al, 2013, p.334).…”
Section: Introductionmentioning
confidence: 99%
“…However many organizations lack procedures and systems to record and recall their learning (Von Zedtwitz, 2002); post project reviews occur infrequently and are often relatively shallow in practice (Blazevic and Lievens, 2004;Busby, 1999). Activities such as formal project review processes, audits, and presentations provide the mechanism for teams to engage in reflective practices which can enhance learning (Newell and Edelman, 2008). This contributes to the effective retention and replication of knowledge developed during NSD (Marsh and Stock, 2003) and stops mistakes being repeated (Storey and Hughes, 2013).…”
Section: Nsd Competenciesmentioning
confidence: 99%
“…It has been found that mere articulation, via interpersonal communication, during project post mortems is insufficient to create learning (Newell and Edelman, 2008). The activity of Learning by itself is of little value.…”
Section: Asychronous Communication and Learning Competencymentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge codification refers to the process of knowledge being transformed into information, a form of message or sets of identifiable rules and relationships, which can be transmitted (Kogut & Zander, 1992). Knowledge codification allows knowledge to be accessed and used by others sometime in the future, and it is not dependent on personal networking (Newell & Edelman, 2008). Converting knowledge into explicit information includes explaining one's own experiences and viewpoints in a way that is understandable to others.…”
Section: Knowledge Creation Sharing and Transfermentioning
confidence: 99%